Human Three-Dimensional Endometrial Epithelial Cell Model To Study Host Interactions with Vaginal Bacteria and Neisseria gonorrhoeae - Łaniewski, Paweł (Infect Immun, 2017)
Colonization of the endometrium by pathogenic bacteria ascending from the lower female reproductive tract (FRT) is associated with many gynecologic and obstetric health complications. To study these host-microbe interactions in vitro, we developed a human three-dimensional (3-D) endometrial epithelial cell (EEC) model using the HEC-1A cell line and the rotating wall vessel (RWV) bioreactor technology. Our model, composed of 3-D EEC aggregates, recapitulates several functional/structural characteristics of human endometrial epithelial tissue, including cell differentiation, the presence of junctional complexes/desmosomes and microvilli, and the production of membrane-associated mucins and Toll-like receptors (TLRs). TLR function was evaluated by exposing the EEC aggregates to viral and bacterial products. Treatment with poly(I·C) and flagellin but not with synthetic lipoprotein (fibroblast-stimulating lipoprotein 1 [FSL-1]) or lipopolysaccharide (LPS) significantly induced proinflammatory mediators in a dose-dependent manner. To simulate ascending infection, we infected EEC aggregates with commensal and pathogenic bacteria: Lactobacillus crispatus, Gardnerella vaginalis, and Neisseria gonorrhoeae. All vaginal microbiota and N. gonorrhoeae efficiently colonized the 3-D surface, localizing to crevices of the EEC model and interacting with multiple adjacent cells simultaneously. However, only infection with pathogenic N. gonorrhoeae and not infection with the other bacteria tested significantly induced proinflammatory mediators and significant ultrastructural changes to the host cells. The latter observation is consistent with clinical findings and illustrated the functional specificity of our system. Additionally, we highlighted the utility of the 3-D EEC model for the study of the pathogenesis of N. gonorrhoeae using a well-characterized ΔpilT mutant. Overall, this study demonstrates that the human 3-D EEC model is a robust tool for studying host-microbe interactions and bacterial pathogenesis in the upper FRT.